Peningkatan Akurasi Klasifikasi Tingkat Kesejahteraan Keluarga di Desa Dukuhbadag Menggunakan Algoritma Decision Tree - Hidayat, Taufik; Kurniawan, Rudi (Universitas Methodist Indonesia, 2024)
The level of family welfare in Dukuhbadag Village, Kuningan Regency, perhaps stems from the desire to understand and discover the elements that contribute to the level of family welfare in the area. The core problem in DukuhBadag Village is that it does not yet have an optimal assessment method to ensure the welfare status of the family. The methodology used namely the Decision Tree Algorithm, was chosen as a tool to provide potential future welfare decisions by applying predictions to guarantee that the information depends on the current collection of data types. This research aims to increase the accuracy of the classification of family welfare levels in the village, by applying the Decision Tree algorithm. The test results show that the application of the Decision Tree algorithm succeeded in increasing the accuracy of the classification of family welfare levels in Dukuhbadag Village, by achieving an accuracy of 72.43%. By predicting the condition of family welfare more accurately, it is hoped that this research can provide valuable information regarding the status of family welfare. This information can be the basis for improving development policies at the village level, ensuring more appropriate and effective aid allocation.